Review on Issues and Aspects of Construction Material Mining in Nepal (Journal of Nepal Geological Society, 2019)
For the development of nation, it is utmost important that infrastructures such as roads, highways, bridges, buildings etc. be constructed throughout the country. Infrastructure development is impossible without construction materials such as stone, aggregates and sand. They are the one used in huge amount in construction work. In this context, the cost of construction materials plays vital role in development process. Lower the cost of these materials, the cost of infrastructure development will be lower. Therefore, emphasis should be given to reduce their supply cost. The supply cost primarily depends on production cost. The production cost is dependent on process of getting the mining license at the desired place, scale of the targeted production, mining mechanization, mining processing and transportation cost. For this the mining must be run systematically and compatibly with concerned rules and regulations. In this paper, some of the legal shortcomings in existing rules and regulations concerned with mining the construction material is outlined that needs to be incorporated or corrected.